Analisis komparatif daya saing ekspor biji kakao antara Indonesia, Pantai Gading dan Ghana: Pendekatan RCA dan CMS - Rizki Vanzza Aji; Zulkarnain Ishak; Mukhlis Mukhlis (Jurnal Ekonomi Pembangunan, 2017)
This study aim is to compare the competitiveness of Indonesia cocoa exports with the main ecporting countries of world cocoa beans such as Ivory Coast and Ghana from 2001 to 2016. The comparable of cocoa commodities are raw cocoa or cocoa beans. This research uses descriptive analysis using Revelaved Comparative Advantage (RCA) and Constant Market Share (CMS) approach. The analysis of Revelaved Comparative Advantage is used to determine the competitiveness level of Indonesian cocoa beans, Ivort Coast and Ghana, while Costant Market Share is used to decompose the export growth of Indonesia cocoa beans, Ivory Coast and Ghana into three determinants of export growth including Commodity Composite Effect, Market Distribution Securities and Effects of Competitiveness. RCA analysis shows Indonesia’s cocoa commodity has a comparative advantage in the international market, while CMS analysis shows that the increase of Inonesia cocoa exports is influenced by the increasing demand of world cocoa.